PENGARUH DIVERSIFIKASI PRODUK TERHADAP KINERJA PEMASARAN PADA PT BANK MANDIRI (PERSERO) TBK KANWIL X MAKASSAR - Abdullah, Wahidah; Faisal, Fahmi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2016)
Competition of Mandiri Bank and the others bank such as BRI, BCA, BNI, and other private banks make BRI bank, BCA and BNI more excellent in the product and the level of earnings growth in 2014. The aimed of this study was to determine how much the influence on the product diversification marketing performance in PT. Bank Mandiri (Persero) Tbk Regional Office X Makassar. Total population is 33.684 from the number of customers over the last year. The samples have taken 100 respondents through decision-probability sampling technique by using the simple random sampling method. This type of research was classified as quantitative. The data collection method in this research was a questionnaire. Processing techniques and data analysis using simple linear regression with hypothesis t-test, the coefficient of determination, correlation coefficients on variables studied. The result of this research is product diversification significantly influence to R- square 59.9% on the performance of marketing at PT. Bank Mandiri (Persero) Tbk Regional Office X Makassar. While a part of other influential factors did not research by the researcher was 40.1%.